Assessment of SARS-CoV-2 infection by Reverse transcription-PCR and serology in the Paris area: a cross-sectional study. Issue 1 (29th December 2020) - Cohen, Robert; Jung, Camille; Ouldali, Naim; Sellam, Aurelie; Batard, Christophe; Cahn-Sellem, Fabienne; Elbez, Annie; Wollner, Alain; Romain, Olivier; Corrard, François; Aberrane, Said; Soismier, Nathalie; et al.
Abstract : Background: Several studies indicated that children seem to be less frequently infected with SARS-CoV-2 and are potentially less contagious than adults. To examine the spread of SARS-CoV-2, we combined both Reverse transcription-PCR testing and serology in children in the most affected region in France, Paris, during the COVID-19 epidemic. Methods: From 14 April 2020 to 12 May 2020, we conducted a cross-sectional, prospective, multicentre study. Healthy controls and pauci-symptomatic children from birth to age 15 years were enrolled by 27 ambulatory paediatricians. A nasopharyngeal swab was taken for detection of SARS-CoV-2 by Reverse transcription-PCR and a microsample of blood for micromethod serology. Results: Among the 605 children, 322 (53.2%) were asymptomatic and 283 (46.8%) were symptomatic. Reverse transcription-PCR and serology results were positive for 11 (1.8%) and 65 (10.7%) children, respectively, with no significant difference between asymptomatic and pauci-symptomatic children. Only three children were Reverse transcription-PCR-positive without any antibody response detected. The frequency of Reverse transcription-PCR SARS-CoV-2 positivity was significantly higher for children with positive than negative serology results (12.3% vs 0.6%, p<0.001). Contact with a person with confirmed COVID-19 increased the odds of Reverse transcription-PCR positivity (OR 7.8, 95% CI 1.5 to 40.7) and serology positivity (OR 15.1, 95% CI 6.6 to 34.6). Conclusion: In an area heavily affected by COVID-19, after the peak of the first epidemic wave and during the lockdown, the rate of children with Reverse transcription-PCR SARS-CoV-2 positivity was very low (1.8%), but that of serology positivity was higher (10.7%). Most children with positive Reverse transcription-PCR results also had positive serology results. Trial registration number: NCT04318431 .